Pentahelix Actor Collaboration: A Case Study of Government Dominance and Stakeholder Engagement in North Lombok - Wahyu Herianto Ardi; Suswanta (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to see how Pentahelix Actor Collaboration in tourism development in North Lombok Regency and what factors influence tourism development. The research method used is qualitative, with primary data sources in the form of interview results with four informants. Q-DAS (Qualitative Data Analysis Software), NVivo 12 plus software, was used to analyze data for this study. The results of this study indicate that the role of government in tourism development is still very dominant, with a percentage of 43%, then the Community is 27%, Academics 12%, Private Sector 9% and Media 7%. And the factors that influence tourism development are Natural beauty and culture with a percentage of 21%, Infrastructure Facilities 21%, HR training 14%, Community Participation 14%, Government Support 17% and Budget Funds 10%.